English Youth Slang Translation Methods - qizi, Mamadiyarova Munisa Abduroziq (Miasto Przyszłości, 2023)
In this article, we attempt to solve the problem of translating the youth slang of the English language in both British and American versions, taking modern youth languages as a material.